HTML, XHTML, and CSS all-in-one for dummies - Harris, Andrew, 1964-; Harris, Andrew, 1964- (Hoboken, N.J. : Wiley ; Chichester : John Wiley [distributor], 2011)
Explains the basics of HTML, XHTML, and CSS, covering such topics as AJAX, client-side programming with JavaScript, server-based programming with PHP, MySQL, and web design.
Creating the HTML/XHTML foundation -- Styling with CSS -- Using positional CSS -- Client-side programming with JavaScript -- Server-side programming with PHP -- Managing data with MySQL -- Into the future wiht AJAX -- Moving from pages to sites.
"Covers HTML5 and prior versions of HTML" -- p. [1] of cover.
Previous ed.: published as HTML, XHTML, and CSS all-in-one desk reference for dummies by Andy Harris and Chris McCulloh. 2008.
Includes index.
Keywords: HTML (Document markup language); XHTML (Document markup language); Cascading style sheets; HTML (Document markup language); XHTML (Document markup language); Cascading style sheets